Congenital Malaria and Its Associated Factors at Issaka Gazobi Maternity of Niamey in Niger - I. Tahirou; M. O. Zara; M. L. Moustapha; M. Kamayé; D. Mahamadou; A. Ibrahim; M. Daou; A. Soumana; M. L. Ibrahim (International Journal of Pediatrics)
Background. Congenital malaria is a serious and common infection in tropical Africa. It has multiple consequences on the newborn and the mother. Objective. The objective of this study is to calculate the prevalence of congenital malaria, describe its clinical signs, and analyze its associated factors. Methodology. It is a cross-sectional and prospective study, conducted at Issaka Gazobi Maternity of Niamey, from June 1 to November 30, 2017. The diagnosis was made by microscopy of a thick and thin blood smear of mother, newborn, and umbilical cord. Results. Two hundred and forty-nine (249) consecutive newborn/mother pairs were included. The prevalence of congenital malaria infection was 26.51% (66/249) with a parasite density of 101 P/μl (SD: 47.3; [80; 320]). The prevalence of congenital malaria disease was 14.06% (35/249) with a parasite density of 108 P/μl (SD: 32.6; [40; 200]. All patients were infected with Plasmodium falciparum. 43% (18/35) of neonates had hyperthermia and did not have a sucking reflex, 8.5% (3/35) were anaemic, 11.42% (4/35) had convulsed, 20% (7/35) had a coma, and 45.71% (16/35) had a low birth weight. No deaths were recorded, and only the nonuse of bed nets was significantly associated with congenital malaria (p=0.04). Conclusion. In Niger, one out of four newborns is infected with Plasmodium. Infection can progress to congenital malaria disease. The use of mosquito nets and intermittent preventive treatment would reduce the incidence of congenital malaria.